Non-indigenous and cryptogenic marine species in the Port of Algiers (Western Mediterranean) - BENSARI, BILEL; BAHBAH, LAMIA; KACIMI, ADEL; BACHETARZI, RYM; BACHARI, NOUR EL ISLAM (Mediterranean Marine Science, 2025)
This study addresses the growing concern of non-indigenous and cryptogenic marine species in the Mediterranean Sea, particularly in high-risk zones such as ports. The Port of Algiers, a significant maritime hub in Algeria, was selected as the study site to document the presence of such species due to its susceptibility to introductions through vessel traffic. Sampling was conducted from 2021 to 2024 across various submerged structures, including mooring buoys and ship fenders. Specimens were collected by scraping surfaces and preserved for identification, which was performed to the lowest taxonomic level possible. The results revealed 18 distinct species, of which 13 were non-indigenous and five cryptogenic. Notably, 11 of these species are recorded for the first time on the Algerian coast. Taxonomically, the species included Ascidiacea (six species), Bryozoa (five species), Crustacea (three species), Polychaeta (three species), and Porifera (one species). This research contributes to the baseline knowledge of non-indigenous and cryptogenic species in Algerian marine environments, providing essential data to support further ecological and biogeographic studies on species introductions in the Mediterranean Sea.